War and Otherness. Images of the Enemy in the Visual Culture, from the Middle Ages to Nowadays: An Introduction - Franco Llopis, Borja (Eikón / Imago, 2020)
Leader article of War and Otherness. The aim of this paper is to present some methodological questions related to the study of Otherness in the last decades, as well as, to connect them with the papers presented for this edited volume.